The Psychology of Loneliness: Understanding Its Causes, Effects, and Paths to Healing - Akram, Muhammad; Umaru, Isaac John; Aslam, Nosheen; Rashid, Abid; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Al-Musawi, Jehan Mohammed; Mahmood, Abid (African Journal of Medicine, Surgery and Public Health Research, 2025)
Loneliness is a deeply personal and multifaceted emotional state that affects millions of individuals across all ages, genders, and cultural backgrounds. Often misunderstood as a temporary feeling, loneliness can have serious implications for both mental and physical health, contributing to conditions such as depression, anxiety, and cognitive decline. This article explores the psychological underpinnings of loneliness, examining how it influences emotional well-being, thought processes, and behavior. It also analyzes the broader social and cultural dynamics, such as digital disconnection, urbanization, and changing family structures that have contributed to its growing prevalence in the modern world. In response, the article discusses a range of evidence-based approaches to addressing loneliness, including public awareness initiatives, therapeutic interventions focused on social reengagement, and lifestyle adjustments aimed at fostering meaningful connections. By highlighting these strategies, the article seeks not only to demystify the experience of loneliness but also to promote resilience and recovery, offering a hopeful perspective on overcoming this often-invisible emotional struggle.